Salinomycin exerts anti‐colorectal cancer activity by targeting the β‐catenin/T‐cell factor complex. (24th July 2019) - Wang, Zhongyuan; Zhou, Liang; Xiong, Yanpeng; Yu, Shubin; Li, Huan; Fan, Jiaoyang; Li, Fan; Su, Zijie; Song, Jiaxing; Sun, Qi; Liu, Shan‐Shan; Xia, Yuqing; et al.
Abstract : Background and Purpose: Salinomycin is a well‐known inhibitor of human cancer stem cells (CSCs ). However, the molecular mechanism(s) by which salinomycin targets colorectal CSCs is poorly understood. Here, we have investigated underlying antitumour mechanisms of salinomycin in colorectal cancer cells and three tumour models. Experimental Approach: The inhibitory effect of salinomycin on the Wnt/β‐catenin pathway was analysed with the SuperTopFlash reporter system. The mRNA expression of Wnt target genes was evaluated with real‐time PCR. Effects of salinomycin on β‐catenin/TCF4E interaction were examined using co‐immunoprecipitation and an in vitro GST pull‐down assay. Cell proliferation was determined by BrdU incorporation and soft agar colony formation assay. The stemness of the cells was assessed by sphere formation assay. Antitumour effects of salinomycin on colorectal cancers was evaluated with colorectal CSC xenografts, APC min/+ transgenic mice, and patient‐derived colorectal tumour xenografts. Key Results: Salinomycin blocked β‐catenin/TCF4E complex formation in colorectal cancer cells and in an in vitro GST pull‐down assay, thus decreasing expression of Wnt target genes. Salinomycin also suppressed the transcriptional activity mediated by β‐catenin/LEF1 or β‐catenin/TCF4E complex and exhibited an inhibitory effect on the sphere formation, proliferation, and anchorage‐independent growth of colorectal cancer cells. In colorectal tumour xenografts and APC min/+ transgenic mice, administration of salinomycin significantly reduced tumour growth and the expression of CSC‐related Wnt target genes including LGR5. Conclusions and Implications: Our study suggested that salinomycin could suppress the growth of colorectal cancer by disrupting the β‐catenin/TCF complex and thus may be a promising agent for colorectal cancer treatment.